Studi Meta-analisis: Pengaruh Penambahan Kultur Starter pada Profil Fermentasi, Mikroorganisme, dan Metabolit Hasil Fermentasi Biji Kakao (Theobroma cacao L.) - Misbakh, Nafila Chaerunnisa; Cempaka, Laras; David, Wahyudi; Asiah, Nurul (Politeknik Negeri Lampung, 2022)
Fermentation of cocoa beans can produce flavour precursors and colour changes in chocolate. Generally, this process is carried out for 5-7 days without adding starter culture. Adding a starter culture is considered to improve the quality of cocoa beans and shorten the fermentation time. The purpose of this study was to compare the starter cultures used in the cocoa bean fermentation process through a meta-analysis approach. Twenty-four related articles have been screened from the initial number of 110 articles. There are five starter cultures and six parameters that can be processed by Confidence Interval (CI) analysis. Calculating p and I2 values ​​using STATA software was performed to see variations between studies and test the significance of their effects during the fermentation process through p values. The variation test between studies showed that the profiles of lactic acid bacteria (LAB) and acetic acid bacteria (AAB) were heterogeneous. While the yeast profile, levels of lactic acid, acetic acid and pH between studies are homogeneous. The results of the study showed that the addition of starter culture will affect the levels of yeast profile (ES: 0.470; 95% CI: 0.371 to 0.569; p = 0.0); LAB profile (ES: 0.747; 95% CI: 0.600 to 0.894; p = 0,0); AAB profile (ES: 0.808; 95% CI: 0.663 to 0.953; p = 0.0); lactic acid (ES: -0.003; 95% CI: -0.162 to 0.156; p = 0.039); acetic acid (ES: 0.189; 95% CI: 0.01 to 0.368; p = 0.039) and pH (ES: 0.109; 95% CI: 0.001 to 0.218; p = 0.049). Using pure starter cultures can increase the number of microbes of the type added and increase metabolic activity by showing a decrease in acetic acid levels in cocoa beans at the end of the fermentation process. However, no changes were seen in pH or lactic acid levels.